Role of Extracellular Vesicles in Cellular Cross Talk in Malaria - Babatunde, Kehinde Adebayo; Yesodha Subramanian, Bibin; Ahouidi, Ambroise Dioum; Martinez Murillo, Paola; Walch, Michael; Mantel, Pierre-Yves (Frontiers in Immunology, 2020)
Malaria infection caused by the Plasmodium species is a complex disease in which a fine balance between host and parasite factors determine the disease severity. While in some individuals, the infection will trigger only a mild and uncomplicated disease, other individuals will develop severe complications which lead to death. Extracellular vesicles (EVs) secreted by infected red blood cells (iRBCs), as well as other host cells, are important regulators of the balance that determines the disease outcome. In addition, EVs constitute a robust mode of cell-to-cell communication by transferring signaling cargoes between parasites, and between parasites and host, without requiring cellular contact. The transfer of membrane and cytosolic proteins, lipids, DNA, and RNA through EVs not only modulate the immune response, it also mediates cellular communication between parasites to synchronize the transmission stage. Here, we review the recent progress in understanding EV roles during malaria.